Oralidade e livro didático: uma possível reconfiguração no ensino de língua portuguesa - Winch, Paula Gaida (2014)
Taking into account the increasing interest of recognizing the oral language as one of the objects of Portuguese Language (LP) teaching, such as writing, reading and grammar are traditionally recognized, and the few researches about the treatment attributed to oral language at Portuguese textbooks (LDP), in this research, developed between 2012 and 2014, from Bakhtin‟s socio-historic and discursive perspective, it was investigated in which measure, the proposals involving oral language, presented at LDP, can promote the development of practices that can result in a rethinking of this language teaching. For that, it was selected as corpus, six LDPs for elementary school, whose sets were approved in the editions of National Program of Textbook (PNLD) of 1999, 2011 e 2014. Through the analysis involving oral language in these textbooks, it was noticed possible signals of a rethinking at LP teaching, considering the relations between oral and written suggested to be established during the development of the proposals: there is a prevalence of approach relations between the language modalities, in which the written is took as a piece of instrument in order to develop the oral expression skills; and there is a meaningful decrease of the proposals based on a dependency relation of oral to written, it means, of oralization of written texts . These signals are also found in the role that is projected to be performed by the teacher and the pupils during the development of the proposals. To the teacher, it is projected a less participative paper, and to the pupil, a more active paper, what is seen due to the detailed explanations, given to the pupil, about the actions to be realized by him in each proposal, and, in the more recent textbooks, due to teacher‟s orientations to be given directly to the pupil. In spite of the advances in the treatment attributed to oral language, it is still visible more worrying with written development, particularly, in the textbooks Português através de textos and Vontade de Saber: Português . Thus, a rethinking in LP teaching, regard to oral language, can be developed in the future, since the oral modality needs to fight for its space as a true teaching object at Portuguese classes.